Elementary school students' ability to understand the elements and properties of simple flat shapes - Triyono, Ageng; Nurimani, Nurimani; Budiono, Budiono (Nashir Al-Kutub Indonesia, 2024)
This research aims to determine: (1) the level of understanding of third grade elementary school students regarding the elements and properties of simple flat shapes, and; (2) distribution of students based on their level of understanding. The research objectives were achieved using a descriptive qualitative research approach. The sample involved was 156 students taken from the population using saturated sampling techniques. Data collection was carried out using a test method which aims to measure students' competence in understanding the elements and properties of simple flat shapes. The collected data was analyzed by calculating the average percentage and standard deviation (SD), which were then converted into categories of student understanding level. The calculation result of the average percentage = 62.37%, and the standard deviation is 21.08. In general, students' level of understanding is in the